Egyptian archaeology and the twenty-first century museum - Stevenson, Alice 1982- (Elements in ancient Egypt in context, 2022)
This Element addresses the cultural production of ancient Egypt in the museum as a mixture of multiple pasts and presents that cohere around collections; their artefacts, documentation, storage, research, and display. Its four sections examine how ideas about the past are formed by museum assemblages: how their histories of acquisition and documentation shape interpretation, the range of materials that comprise them, the influence of their geographical framing, and the moments of remaking that might be possible. Throughout, the importance of critical approaches to interpretation is underscored, reasserting the museum as a site of active research and experiment, rather than only exhibitionary product or communicative media. It argues for a multi-directional approach to museum work that seeks to reveal the inter-relations of collection histories and which has implications not just for museum representation and documentation, but also for archaeological practice more broadly